OC-069 Randomised Controlled Trial – Transcutaneous Auricular Electrical Vagal Nerve Stimulation Prevents the Development of Acid Induced Esophageal Hypersensitivity. (17th August 2016) - Amarasinghe, G; Aziz, Q; Farmer, AD
Abstract : Introduction: We have previously demonstrated that physiologically increasing vagal tone, with deep breathing, prevents the development of acid induced oesophageal pain hypersensitivity. 1 We aimed to determine whether electrical manipulation of parasympathetic tone influences the development of hypersensitivity in a validated model of acid induced oesophageal pain. Methods: Prior to, and following, a 30 minute distal oesophageal infusion of 0.15 M hydrochloric acid, pain thresholds to electrical stimulation were determined in the proximal non-acid exposed oesophagus in 15 healthy subjects (11 male, mean age 30 years, range 21–42). Validated sympathetic (cardiac sympathetic index) and parasympathetic (cardiac vagal tone) parameters were measured at baseline and continuously thereafter. Subjects were randomised in a blinded crossover design to receive either external auricular electrical vagal nerve stimulation (VNS), or sham stimulation, during acid infusion. Results: VNS increased cardiac vagal tone (31.6% ± 58.7 vs. -9.6 ± 20.6, p = 0.02) in comparison to sham stimulation. Mixed effects linear regression, controlling for age and gender, demonstrated that VNS prevented the development of acid-induced oesophageal hypersensitivity in comparison to sham stimulation (coefficient 15.4 mA /unit time (95% confidence interval 8.8 to 22.2), p = 0.001). Figure 1 demonstrates the percentage change in pain thresholds following a 30 distal oesophageal acid infusion. Conclusion: The development of oesophageal hyperalgesia is prevented by electrically stimulating the vagus nerve by increasing parasympathetic tone. This study provides further evidence of the anti-nociceptive role of the parasympathetic nervous system within the oesophagus. Further work is warranted in patients groups such as those with recalcitrant non-erosive reflux disease. Reference: 1 Botha C, et al . Gut 2014. Disclosure of Interest: None Declared